Perceived organizational support on employee performance: the mediating role of organization-based self-esteem - Eko Prasetyo; Anang Kistyanto; Jun Surjanti (Journal of Business and Management Review, 2022)
The purpose of this paper is to evaluate the influence of perceived organizational support on employees’ performance through organization-based self-esteem in general banking sector in East Java, Indonesia. Data were collected from general banking sector employees through a self-administered questionnaire survey where a total of 129 questionnaires were distributed. A total of 100 completed questionnaires were received. The hypothesis was tested using an approach structural equation modeling-partial least squares (SEM-PLS) supported by program computer software Smart-PLS 3.0. This pilot study reveals that high perceived organizational support positively affect employees’ performance in general banking sector in East Java, Indonesia. Moreover, organization-based self-esteem levels would mediate the influence of perceived organizational support on employees’ performance in general banking sector in East Java, Indonesia. This study proposes managers to give chances to proficient advancement, improved occupation and satisfying the necessities identified through deference, mindfulness and endorsement. Furthermore, they ought to make more good working conditions, for example, preparing chances to support workers in their wants for self-improvement and accomplishment. This kind of research has not been thoroughly or even not been discussed in academic research. Therefore, it was necessary to put this issue into a management science.